Implementasi Model Pembelajaran Numbered Head Together Pada Mata Pelajaran Fiqih di MA Nurul Yaqin - Fina Andriyanti Andilau; Ibnu Chudzaifah (IAIN Sorong, 2017)
The research in this thesis is motivated by the low student learning outcomes in Islamic Religious Education (PAI) subjects caused by Islamic Religious Education (PAI) teachers in presenting subject matter which is sometimes monotonous. Teachers are more likely to use the lecture method in learning, thereby making students bored. Therefore, researchers chose one of the cooperative learning models namely the Numbered Head Together (NHT) model to improve student learning outcomes. This model uses a grouping system with 4-6 members, which in the implementation phase includes the numbering, asking questions, thinking together and answering questions. This research is a classroom action research (CAR) conducted at Sorong Public High School 2, which aims to improve the learning outcomes of Islamic Religious Education (PAI) students by using the cooperative learning model type Numbered Head Together (NHT). The subjects of this study were students of class XII Science 3 of SMA Negeri 2 Sorong in the odd semester of the 2015/2016 academic year totaling 22 people. This research was conducted in 2 cycles, namely the first cycle and the second cycle was held 2 meetings. Data retrieval is done using learning outcomes tests and observation sheets. The collected data were analyzed both quantitative and qualitative data. Quantitative data is calculated using the SPSS 16.0 formula. The results obtained after the action are given, namely: (1) the activeness of students during the learning process in the classroom has increased, (2) in the first cycle the average score of the Islamic Religious Education learning outcomes (PAI) of students is 71.91 are in the medium category and in the second cycle the average score of the test results of Islamic Religious Education (PAI) students was 88.50 in the high category, (3) in the first cycle the number of students who thoroughly studied in Islamic Religious Education (PAI) was 11 people ( 50%), while in cycle II the number of students who have finished learning is 20 people (90.91%), and (4) the students' responses to the Numbered Head Together (NHT) type of cooperative learning model are 95.45%. From the results of this study, in general, it can be concluded that an increase in learning outcomes of Islamic Religious Education (PAI) class XII students of Sorong Public High School 2 after applying the Numbered Head Together (NHT) type of cooperative learning model.